Condensation heat transfer characteristics of moist air outside 3-D finned tubes with different wettability. (15th September 2020) - Gu, Yuheng; Ding, Yudong; Liao, Qiang; Fu, Qian; Zhu, Xun; Wang, Hong
Abstract: The condensation heat transfer of moist air plays an important role in industries and daily life. However, the presence of non-condensable gases makes it difficult for steam to condensate on a cooling surface. According to previous studies, a three-dimensional (3-D) finned tube and dropwise condensation can both increase the heat transfer performance. To increase the condensation heat transfer of moist air, this study combined these two methods and experimentally studied the condensation heat transfer of moist air outside 3-D finned tubes with different wettability values. The effects of the 3-D fins and surface wettability on the heat transfer process under different steam mole fractions, moist air temperatures, and cooling water inlet temperatures were determined and analysed in detail. The experimental results showed that a hydrophilic 3-D finned tube could achieve the highest heat transfer coefficient, which was up to 94% higher than that of a hydrophilic smooth tube. In addition, the heat flux and heat transfer coefficient increased with decreases in the moist air temperature and cooling water inlet temperature, or with an increase in the steam mole fraction. Droplet retained between 3-D fins increased the diffusion resistance of water steam and the conductive thermal resistance. Highlights: The condensation heat transfer of moist air outside three-dimensional finned tubes was experimentally studied. The influences of the 3-D fins and surface wettability were analysed based on the heat transfer results. The influences of the water steam fraction, moist air temperature, and cooling water inlet temperature were determined. The hydrophilic 3-D finned tube had the best heat transfer performance.